Early Breastfeeding Initiation in Indonesia - Aulia Lisna; Rika Yumna Afifah Arifin; Rizki Ari Anjasmara (UHAMKA Press, 2019)
Breastfeeding exclusive around the world given in infants only about 32,6 million from babies born 136,7 million, in developing countries only about 39 % given breastfeeding by his mother, it was far from the target who want to 80 %.The purpose of this article is to know implementation and nursing (early breastfeeding initiation - IMD) breastfeeding exclusive in the world and the Indonesian descriptive study is based on the implementation of showing limited the exclusive breastfeeding in the world and in Indonesia. Facilitate of IMD still less than optimal.